PRAWIROTAMAN AS KAMPUNG INGGRIS AND THE IMPROVEMENT OF STUDENTS MOTIVATION IN LEARNING ENGLISH FOR - Hernadi, Nour Ardiansyah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Sekolah Tinggi Pariwisata Ambarrukmo Yogyakarta, 2020)
Yogyakarta is not only the city with favorite tourist destinations in Indonesia but also as an education city with students from around the countries and cities. Prawirotaman is a part of the area in Yogyakarta which is known as Kampung Inggris. This area has good potential in influencing and improving the students' motivation in learning English, especially for tourism students, because there are so many foreigners who stay in that area. With that atmosphere, the student can improve their English by practice with the native speakers. This research used a descriptive qualitative method. The purpose of this research is to find out the impact of Prawirotaman in increasing the students’ motivation in learning English. This research shows that Prawirotaman has a good influence on the students who want to learn English directly with native speakers. Keywords: Prawirotaman, Kampung Inggris, Students Motivation, Learning English